Identification of pp120, an endogenous substrate for the hepatocyte insulin receptor tyrosine kinase, as an integral membrane glycoprotein of the bile canalicular domain. - Margolis, R N (1988)
An endogenous membrane-bound substrate of the insulin receptor beta-subunit tyrosine kinase in liver, pp120, has been identified as HA4, a 110-kDa membrane glycoprotein localized primarily to the bile canalicular domain of the hepatocyte. HA4 has been implicated in bile salt transport and cell adhesion. Monoclonal antibodies to HA4 were used to identify it as a substrate of the insulin receptor kinase. Anti-pp120 and anti-HA4 were found to cross-react, and phosphopeptide maps for each of the corresponding antigens were identical. The identification of pp120 as HA4 serves to link insulin action through the receptor tyrosine kinase activity to bile metabolism and raises questions pertaining to the intracellular site(s) of action of the insulin receptor.